Mental Stress Education: The Changes in The Life and Conditions of Patients - M. R. Arpentieva; Asnul Dahar Minghat; G. K. Kassymova (Indonesian Journal of Community and Special Needs Education, 2022)
The goal of this study was to look at the issues of anticipating and reducing stress caused by changes in a person's life (patient). This study looked at patient narratives as one of the most effective types of psychotherapeutic work with adults, especially work geared at masculine development. We paid specific attention to the issues with signal metaphors and psychological transformation triggers. The research technique was based on a theoretical understanding of the issues of anticipating and reducing the stress of life changes (patient). The key findings of this study revealed that the patient overcome liminality or estrangement from himself and the world. In a person's life, a metaphor serves as both a signal and a trigger for change. Then, its use, in one way or another, discloses zones that are vulnerable to change and encourages change. Metaphors can be found in a variety of archetypal frameworks as well as specific role model metaphors. They allow you to assess the patient's internal movement toward the achievement of a specific motivation or intention, encourage upward and/or slow down downward goals, and understand how the patient perceives external changes and how he reacts to change stress.